An empirical analysis of the influence of team success on Indian sports fans' purchase behaviour. (8th June 2023) - Rai, Jaskirat Singh; Yousaf, Anish; Itani, Maher N.; Singh, Amanpreet
This study explores the relationships between team success and sports fans' purchase behaviour. It examines the strength of the mediating role of team brand equity, attitude towards sponsorship, and attitude towards sponsors' brands in such relationships. The study analysed the responses of 602 fans of the Indian Premier League (IPL) using structural equation modelling. A constructive role for team success is confirmed in creating team brand equity for sports fans. The team's success positively impacts on fans' attitudes towards sponsorship importance and attitude towards the sponsor brand but did not influence their purchase behaviour directly. Nevertheless, it indirectly impacts on fans' purchase behaviour with attitude toward sponsor brands as a mediator. Study findings add new insights that advance the understanding for marketing managers of fans' collective attitudes toward sponsorship importance, sponsored brands, and purchase behaviour.